An eco-friendly approach to control Oxya velox infestation: Mangifera indica exoglucanase and endoglucanase cellulose ingestion inhibition activity. (April 2017) - Kanwal, Qudsia; Anwar, Aneela; Akbar, Samina; Iqbal, Munawar; Najaf Iqbal, Dure; Nisar, Numrah; Hussain, Ishtiaq
Abstract: Oxya velox (Grasshopper ) is considered to be one of the damaging pests. The Mangifera indica ( M. indica ) crude enzyme extracts (5 g powder/20 mL of water, ethyl acetate, butanol and chloroform separately) were evaluated for their cellulose ingestion inhibition activity in O. velox . The extracts activities were studied as a function of substrate concentration, pH and temperature. Dinitrosalisalic acid (DNSA) method was adopted to study the kinetic of both endoglucanase and exoglucanase enzymes. The Km values of both enzymes were recorded to be 2 mg/mL and 0.92 mg/mL, respectively, which revealed greater affinity of enzymes for the substrate. All solvents showed considerable enzymes inhibition activity and variation among solvents was insignificant. Results revealed that the cellulose digestion by O. velox enzymes could possibly be inhibited using M. indica extracts. Graphical abstract: fx1 Highlights: Exoglucanase and endoglucanase inhibition activities of Mangifera indica were tested. Grasshopper was used as a test organism. Activities were studied as function of substrate concentration, pH and temperature. M. indica leave extracts revealed potential to inhibit tested enzymes activities.